Bacterial foraging optimization algorithm based on normal cloud model for forward kinematics of a 4-DOF parallel manipulator. Issue 1 (12th August 2022) - Shenli, Wu; Xiaoming, Liang; Ling, Liu; Zimeng, Yao
Abstract: For the 4-SPU parallel mechanism, the complex multivariate nonlinear equation of the forward kinematics solution is transformed into a minimization problem. This article proposes a new bacterial foraging optimization algorithm based on normal cloud model to obtain the solution of the forward kinematics. Adaptive dynamic adjustment of walking step size of normal forward cloud generator is adopted to improve the fixed step size. Y conditional cloud generator is used to dynamically adjust the migration probability. The simulation results show that new algorithm is an effective method to solve the forward solution optimization with high precision and high speed.